2012
DOI: 10.1017/s1355617712000057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neuropsychological Impairment and Vocational Outcomes in Systemic Lupus Erythematosus and Multiple Sclerosis Patients

Abstract: Systemic lupus erythematosus (SLE) and multiple sclerosis (MS) are chronic immunologic diseases that can cause cognitive dysfunction. MS is a central nervous system (CNS) disease characterized by demyelination and progressive brain atrophy. SLE is an autoimmune disease capable of damaging multiple organ systems, including the CNS. Cognitive disturbances are seen in both SLE and MS. The present study is concerned with understanding the similarities and differences between the cognitive profiles of SLE and MS as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…10 In addition, important relationships between executive function and employment have sometimes been shown to be mediated by fatigue. 15 Depression research has also yielded inconsistent findings, with one study finding the opposite result of what has been typical, with the employed group having higher depression scores than the unemployed group. 10 Some of these inconsistencies may have been due to different operationalizations of these factors across studies.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…10 In addition, important relationships between executive function and employment have sometimes been shown to be mediated by fatigue. 15 Depression research has also yielded inconsistent findings, with one study finding the opposite result of what has been typical, with the employed group having higher depression scores than the unemployed group. 10 Some of these inconsistencies may have been due to different operationalizations of these factors across studies.…”
Section: Methodsmentioning
confidence: 97%
“…[6][7][8][9][10][11] Other MS symptom-related factors have also been found to predict employment status, including fatigue, 10,12 depression, [6][7][8] motor difficulties, 13 and cognitive problems. 14,15 More specifically, regarding cognitive problems, scores on tests of processing speed, verbal fluency, working memory, and long-term memory are typically lower in unemployed versus employed individuals with MS. 8,16,17 With all this said, research on cognition and depression has produced inconsistent findings. Regarding cognition, although most studies have found it to be associated with employment status, some have not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 These neuropsychological findings included deficits in working memory and processing speed and general lower cognitive scores, even in the absence of a diagnosed neurologic or psychiatric condition. 7,8 It is possible that these cognitive disturbances may be attributed to decreased WM integrity, the presence and extent of WM lesions, or GM damage, all of which are present in patients with MS and those with SLE. 2,3,[8][9][10] Unlike in MS, the relationship between cerebral pathology and resulting neuropsychiatric disorders in SLE is not well-established.…”
mentioning
confidence: 99%
“…7,8 It is possible that these cognitive disturbances may be attributed to decreased WM integrity, the presence and extent of WM lesions, or GM damage, all of which are present in patients with MS and those with SLE. 2,3,[8][9][10] Unlike in MS, the relationship between cerebral pathology and resulting neuropsychiatric disorders in SLE is not well-established. Neuropsychiatric symptoms range from transient to chronic and are heterogeneous among patients.…”
mentioning
confidence: 99%